Contrasting styles of (U)HP rock exhumation along the Cenozoic Adria‐Europe plate boundary (Western Alps, Calabria, Corsica). (15th June 2015) - Malusà, Marco G.; Faccenna, Claudio; Baldwin, Suzanne L.; Fitzgerald, Paul G.; Rossetti, Federico; Balestrieri, Maria Laura; Danišík, Martin; Ellero, Alessandro; Ottria, Giuseppe; Piromallo, Claudia
Abstract Since the first discovery of ultrahigh pressure (UHP) rocks 30 years ago in the Western Alps, the mechanisms for exhumation of (U)HP terranes worldwide are still debated. In the western Mediterranean, the presently accepted model of synconvergent exhumation (e.g., the channel‐flow model) is in conflict with parts of the geologic record. We synthesize regional geologic data and present alternative exhumation mechanisms that consider the role of divergence within subduction zones. These mechanisms, i.e., (i) the motion of the upper plate away from the trench and (ii) the rollback of the lower plate, are discussed in detail with particular reference to the Cenozoic Adria‐Europe plate boundary, and along three different transects (Western Alps, Calabria‐Sardinia, and Corsica‐Northern Apennines). In the Western Alps, (U)HP rocks were exhumed from the greatest depth at the rear of the accretionary wedge during motion of the upper plate away from the trench. Exhumation was extremely fast, and associated with very low geothermal gradients. In Calabria, HP rocks were exhumed from shallower depths and at lower rates during rollback of the Adriatic plate, with repeated exhumation pulses progressively younging toward the foreland. Both mechanisms were active to create boundary divergence along the Corsica‐Northern Apennines transect, where European southeastward subduction was progressively replaced along strike by Adriatic northwestward subduction. The tectonic scenario depicted for the Western Alps trench during Eocene exhumation of (U)HP rocks correlates well with present‐day eastern Papua New Guinea, which is presented as a modern analog of the Paleogene Adria‐Europe plate boundary.